THE INFLUENCE OF CHARACTERISTICS ON DIFFERENT ELEMENTS OF COMPENSATION SYSTEM TOWARD MOTIVATION - ARLEEN HERAWATY; ELLA AULIA (Jurnal Bisnis dan Akuntansi, 2005)
Employee is one of the most valuable resources for the company. One factor that could make the company succeed is its employee performance. Performance evaluation is one of the qualitative measurements for giving the compensation for employee. This research aimed to determine whether the transparency, fairness, and controllability as characteristics on compensation system could influence the employees’ motivation in the company. Data for this research using questionnaire that being sent to employees in companies. Multiple regressions were used to test the hypothesis. Result of this research showed that perceived transparency and perceived fairness of the different elements of the compensation system significantly influences the extrinsic motivation. Perceived controllability over the different elements of the compensation system significantly has a positive relationship with extrinsic motivation. The perception of transparency, controllability and fairness of the monetary part of the compensation system has no significant effect on intrinsic motivation. The perception of transparency, controllability and fairness of the promotion opportunities has a positive and significant effect on intrinsic motivation. The perception of transparency, controllability and fairness of the compensation system has no significant influence towards motivation level indicator.